Efektivitas Latihan Peregangan Otot Terhadap Penurunan Tingkat Nyeri Punggung Bawah Pada Perawat - Riski Amalia; Mursal; Irfanita Nurhidayah; Novianti (MEDIA ILMU KESEHATAN, 2022)
Background: Lower back pain health problems generally occur in nurses, which can limit nurses in providing patient care and absence from work. Lower back pain can cause a decrease in the quality and productivity of work in hospitals.Objective To determine the effectiveness of muscle stretching exercises in reducing lower back pain in nurses at Palang Merah Indonesia Hospital in North Aceh.Methods: This study is a Quasi Experiment with a pretest-posttest design and no control group. In this study, the researcher used 30 samples using purposive sampling techniques. The instrument used in this study was the Numerical Rating Scale (NPRS). The data analysis used was a paired t-test.Results: Based on the current findings of this study, the effectiveness of muscle stretching exercises in decreasing the level of the lower back in nurses (p< 0.05).Conclusion: The effectiveness of muscle stretching exercises in reducing low back pain in nurses. Still, nurses need stretching exercises and strengthening variations with stretching or aerobic exercises to prevent lower back pain levels